Efficiency of surface inactivation disinfectants for bacteria studied in an aquaculture microbiology laboratory - Manfred Weidmann (Journal of Biosafety and Biosecurity, 2023)
Routine microbial inactivation procedures used in microbiology laboratories must be verified. In this study, the efficacy of surface disinfection using 70% Isopropanol, 0.45% Presept, and 1% Virkon was tested against 24 bacterial strains commonly handled in aquaculture microbiology laboratories. Isopropanol was ineffective against Nocardia asteroides NCIMB 1290, while Virkon was not effective against Aeromonas eucrenophila NCIMB 74 or Pediococcus acidilacti R52037.